Implementation of Variative Methods Based on a Scientific Approach to Improve the Understanding of Islamic Jurisprudence in Elementary Madrasah Students - Wulan Octi Pratiwi; Nelly Herawati Jasuma; Eri Purwanti (Journal of Adaptive Education, 2025)
This study aims to describe the implementation of a variety of methods based on a scientific approach to improve students' understanding of Islamic jurisprudence (fiqh) at Nurul Hidayah Roworejo Elementary School. The study used a qualitative approach with data collection techniques through interviews and observations. The research respondents consisted of Islamic jurisprudence teachers and the principal of the school. The results showed that teachers implemented various methods, such as lectures, questions and answers, discussions, and demonstrations, combined with the steps of the scientific approach, namely observing, asking, exploring, associating, and communicating. However, several obstacles were found, including limited reading materials and learning media, teachers' suboptimal understanding of the scientific approach, and a lack of support for facilities and infrastructure. Improvement efforts were made through increasing teacher creativity in developing learning media, searching for alternative learning resources, and expanding discussion spaces with students. In addition, support from the principal in providing facilities and training is essential to improve the effectiveness of curriculum implementation. This study recommends synergy between teachers and schools to strengthen the quality of Islamic jurisprudence learning at the Elementary School.